1990
DOI: 10.1210/endo-126-5-2534
|View full text |Cite
|
Sign up to set email alerts
|

Development of Valid Methods to Measure Insulin-Like Growth Factors-I and -II in Bone Cell-Conditioned Medium*

Abstract: A variety of human cells and biological fluids have been shown to produce or contain insulin-like growth factor (IGF)-specific binding proteins (BPs). The existence of these BPs in serum and conditioned medium of cell and organ cultures has complicated radioligand assays for measurement of IGFs. Various strategies have been proposed to avoid interference of BPs with these assays, including acid-ethanol precipitation of BPs and acid-gel filtration. Many of these procedures are time consuming, exhibit low recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The difference in cortical thickness between C3H and B6 mice appeared to be caused by significantly smaller endosteal circumference in C3H mice (approximately 20% less) compared with B6 mice. The increase in cortical thickness of approximately 25% during puberty (days [23][24][25][26][27][28][29][30][31][32][33][34][35] in both strains of mice appeared mainly to be caused by increased periosteal circumference, because the endosteal circumference did not show significant change during this period (Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The difference in cortical thickness between C3H and B6 mice appeared to be caused by significantly smaller endosteal circumference in C3H mice (approximately 20% less) compared with B6 mice. The increase in cortical thickness of approximately 25% during puberty (days [23][24][25][26][27][28][29][30][31][32][33][34][35] in both strains of mice appeared mainly to be caused by increased periosteal circumference, because the endosteal circumference did not show significant change during this period (Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, serum levels of IGF-I and osteocalcin provided statistically significant contributions to the prediction of various bone parameters (Table 3). To further evaluate the relative contribution of the previously mentioned five independent variables to predict the gender differences in bone size, we performed multiple regression analyses using data from prepubertal (days 7-23), pubertal (days [23][24][25][26][27][28][29][30][31][32][33][34][35], and postpubertal (days 35-56) periods. We found that the relative contribution of gender to differences in periosteal circumference was much greater during the postpubertal period than the prepubertal period (␀-coefficient of 0.36 vs. 0.11).…”
Section: Richman Et Almentioning
confidence: 99%
“…Louis Underwood and Judson Van Wyk, University of North Carolina, Chapel Hill), at a dilution of 1:6,000, as described previously (29). IGF-binding protein artifacts (30) in the IGF-I RIA or in the IGF-I1 radioreceptor assay (RRA; see below) were removed by preincubating samples with an excess of IGF-I1 or IGF-I, respectively, as described by Mohan et a1 (31). The cross-reactivity of IGF-I1 in the IGF-I RIA was <0.5%.…”
Section: Methodsmentioning
confidence: 99%
“…IGF-I1 concentrations were determined by RRA, using H-35 rat hepatoma cells (American Type Culture Collection, CRL 1548) as the receptor source (32). Human IGF-I1 purified from bone matrix (33) was used as standard and tracer, and the assay was performed as described elsewhere (31). The sensitivity of the RRA was -0.4-0.6 ng/well (4-12 ng/ml); the range of the assay was 8-250 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…(i) IGF-I was determined by RIA using recombinant human IGF-I (CIBAGeigy) as tracer and as standard and rabbit polyclonal antiserum UB 286 (kindly provided by Louis Underwood and Judson Van Wyk, University of North Carolina) at a dilution of 1:6000 as described (31). Artifacts known to be produced by the presence of IGF-binding proteins (32) in IGF-I RIA or in IGF-II radioreceptor assay (see below) were eliminated by preincubation of samples with excess IGF-I or IGF-II as described (33 (Table 1). At 9 weeks, 17fl-estradiol-treated rats had gained less weight than the untreated animals.…”
mentioning
confidence: 99%